Metaphors in Ismail Hashim’s photography / Roba Abdullah Alromih - Roba Abdullah , Alromih (2018)
This study focuses on the selected artwork of Ismail Hashim, particularly those that focus on his exploration on the concepts of time, memory and our place in society. Another theme that this study examines is his preoccupation with labour and his identification with the working class. The major strength of Ismail Hashim’s art is his sensitivity and ability to send a profound message through what appears to be simple objects and normal everyday activities. While the work may seem ordinary at first, the combination of his compositional methods, portrayal of subject matter and the titles of the work show his thought process and reveal that he is concerned with more than just the ordinary. It reveals that he is also concerned with the philosophical or existential questions of life and the capability of photography as a medium to consider those questions. This research uses a qualitative methodology that includes archival research, literature review, face to face viewing of artworks, documentation of artworks and a formal visual analysis. Contextual information is gathered from published books, scholarly articles, published interviews and is used to support the arguments made. The conceptual framework is based on the Conceptual Metaphor Theory (CTM) by Lakoff & Johnson (1980) which explains how metaphors can be an effective way to explain new abstract ideas using tangible characteristics associated to a familiar existing concept. And Suzanne Langer’s concept of symbolism in art is used to explore how Ismail Hashim’s use of simple objects like chairs and postboxes are symbolic of the working class, they can help us understand his views of the act of labour as a necessary act of both pain and pleasure